A longitudinal study on the relationships between impulsivity and excessive smartphone use among patients with acquired brain injury and control participants - Wacks, Yehuda; Koslowsky, Meni; Bloch, Ayala; Weinstein, Aviv (Frontiers in Psychiatry, 2025)
IntroductionPrevious studies have demonstrated that impulsivity is positively correlated with excessive smartphone use, indicating the involvement of frontal lobe circuits. This study examined excessive smartphone use, impulsivity, and mental wellbeing in patients with acquired brain injury (ABI) before and after occupational rehabilitation treatment, and control participants.ProcedureParticipants consisted of 44 patients with ABI [10 patients with orbitofrontal syndrome (OFS) and 34 without OFS] and 69 control participants with no history of brain injury. The procedure included a smartphone application that tracked daily smartphone use and frequency of device unlocks, computerized tasks that evaluated impulsive choice (Delay Discounting Task), impulsive action or response inhibition (the ability to stop an already-initiated action—the Go/No-Go task), and questionnaires measuring excessive smartphone use, obsessive–compulsive symptoms [Yale–Brown Obsessive–Compulsive Scale (YBOCS)], impulsivity [Barratt Impulsiveness Scale (BIS-11), which measures non-planning, motor and attention impulsivity], and mental wellbeing [Depression, Anxiety, and Stress Scale (DASS-21), which measures depression, anxiety, and stress]. Data were collected at two time points: baseline (T1) and 5 months later (T2).ResultsAt baseline (T1), patients with ABI and OFS exhibited higher impulsive action, indicated by more commission errors on the Go/No-Go task, excessive smartphone use, and higher ratings of depression compared with control participants. Secondly, patients with ABI without OFS showed higher trait attention-impulsivity ratings compared with control participants. After treatment (T2), patients with ABI showed improved impulsive choice, indicated by improved delay discounting, but no improvement in smartphone use.DiscussionBrain injury, particularly in frontal regions, is associated with impulsiveness and excessive smartphone use. Patients with ABI showed an improvement in delay discounting after treatment, which is likely due to occupational therapy and training in control of impulsivity. It is recommended that specific treatment program for excessive smartphone use will be developed for patients with ABI.